2015
DOI: 10.1155/2015/850184
|View full text |Cite
|
Sign up to set email alerts
|

Low Back Pain in Athletes Is Associated with General and Sport Specific Risk Factors: A Comprehensive Review of Longitudinal Studies

Abstract: We aimed to examine systematically the available evidence on risk factors of low back pain (LBP) in athletes. We performed search without language restriction in PubMed, Ovid, Google Scholar, Scopus, and CINAHL. Longitudinal studies that examined possible risk factors of LBP in athletes were included in this systematic review. Based on methodological quality of studies, a best-evidence synthesis was conducted. Seven longitudinal studies were included, four of which had high methodological quality. Results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 39 publications
0
41
0
1
Order By: Relevance
“…On average LBP positive subjects had 3.1 ± 3.0 LBP episodes lifelong. However, none of the subjects declaring the LBP symptom had a specific medical diagnosis [ 7 ], accordingly, they were non-specific LBP cases [ 9 , 10 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…On average LBP positive subjects had 3.1 ± 3.0 LBP episodes lifelong. However, none of the subjects declaring the LBP symptom had a specific medical diagnosis [ 7 ], accordingly, they were non-specific LBP cases [ 9 , 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…At present, the scientific interest in the risk factors for LBP is increasing both for athletic performance and health implications [ 9 , 10 ]. Further research is required in this field because discrepancies exist among studies especially regarding LBP prevalence, causes, and therapeutic strategies [ 9 , 12 , 35 ]. In addition, sex-specific studies are warranted to take into account sex differences in factors potentially modulating LBP [ 10 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[15] Another study done by Moradi et al, found that decreased lumbar flexion and decreased lumbar extension are positively associated with LBP. [16] This study found that participants with below 25 abdominal repetitions are 1.35 times more likely to have LBP as compared to 25 repetitions and above. Koley et al, showed the correlation of nonspecific LBP (NSLBP) and aged-matched controls who found a positively significant correlations (P < 0.05) of abdominal muscle endurance with NSLBP.…”
Section: Trunk Flexors and Extensors Range Of Motion Using A Gravity mentioning
confidence: 64%